Architectural tiles : conservation and restoration : from the medieval period to the twentieth century - Durbin, Lesley (Butterworth-Heinemann series in conservation and museology., 2005)
Providing hands on advice for the conservator, Architectural Tiles: Conservation and Restoration is a unique and valuable guide. Topics covered offer practical guidance on conservation and restoration techniques including the problems of manufacture, cleaning, replacement or repair and mortars. Techniques are illustrated by comprehensive case studies, against a background of the role of past architects and designers in historic schemes.